Tradisi Sambatan Sebagai Pendidikan Karakter Berbasis Kearifan Lokal Dalam Pembelajaran IPS di Sekolah Dasar - Wibi Wijaya (Bakaba, 2022)
The sambatan tradition is a tradition that comes from the Javanese tribe and the tradition will be carried wherever the people are. The sambatan tradition is reflected in the daily social life of the community. The philosophy of this tradition is a sense of helping others and a sense of mutual cooperation and its relation to character building in learning in elementary schools. In line with the Indonesian government which will revolutionize the nation's character through strengthening character education. The purpose of this study was to examine the value of the sambatan tradition in character building in social studies learning in elementary schools. This type of research is qualitative research. The determination of informants was carried out by purposive sampling with a total of 17 people. Data collection techniques were carried out by observation and in-depth interviews. The results of this study can be concluded that the decline in the morality of young people who are still teenagers can be suppressed by the sambatan tradition without looking at ethnic differences and other differences. The community's concern for the interests of others is very much reflected in Koto Tangah Padang starting from children, teenagers to adults in helping other people who need help. Then the second result is that social studies learning in elementary schools is quite effective in instilling an attitude of helping others. This can be seen in the activities provided by the teacher to students both in the form of theory and practice in the school environment.